The preferential option for the poor: a contextual reading of John Wesley’s social ethics in contemporary Zimbabwe - Dimingu, Wilfred (Midlands State University, 2015)
Poverty has become one of the major challenges in Zimbabwe since the turn of the millennium. This period has been characterized by high levels of unemployment and economic contraction. This seeks revisit John Wesley’s social ethic of preferential option for the poor in light of the economic challenges the Zimbabweans have been facing and the plight of the poor. This study looked at how John Wesley confronted the poverty situation in eighteenth century Britain. It further looked at the how John Wesley’s social ethics can be used to address the problems that are being faced in contemporary Zimbabwe. Lastly this study took the position that although the specific economic order that confronted John Wesley were peculiar to the eighteenth century his thoughts can provide the Zimbabweans with an entry point in addressing their contemporary problems.